Level of social disclosure of Brazilian companies regarding the sustainable development objectives of United Nations (UN): A study of the dissemination of the objective of gender equality - Garcia, Editinete Andre da Rocha; Araújo, Isnara Anterio; Albuquerque Filho, Antonio Rodrigues (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This paper aims to verify if the companies that prepared their reports observing the Global Reporting Initiative (GRI) standard and that were submitted to an auditand if the companies that are part of the Corporate Sustainability Index (ISE) portfolio adopt greater disclosure of gender equality. It was analyzed 61 sustainability reports published in 2019, in the GRI standard. From the adoption of a quantitative method, the results of the study demonstrate that Brazilian companies have an average level of 51.9% disclosure of the GRI guidelines related to SDG5. Furthermore, It was found that the assurance of the reports positively affects the disclosure of the SDG5, while the company's participation in the ISE did not present statistical significance.